Analisis Manajemen Sistem Pemeliharaan Alat Kesehatan - mugi mugiyanto; Muslihun; Annisa Ekma Nurani (MEDIKA TRADA, 2025)
Abstrak Maintenance of medical equipment is very necessary and is even a priority in important programs in a health service. As per the Regulation of the Minister of Health (Permenkes) Number 15 of 2023. concerning the maintenance of medical devices in health service facilities. More specifically, as mandated by Law Number 44 of 2009 concerning Hospitals, medical equipment must be tested and calibrated. The purpose of this study is to determine the correct method and procedure for maintaining medical devices. While the purpose of maintaining the device is to maintain the level of accuracy of the device and to be able to operate properly. This study uses the Literature Review Article method using 15 journals as data sources which are electronic data. The results of this study contain several aspects in the maintenance of health equipment. In addition, from various literatures, it can be concluded that there is a significant relationship between tool maintenance and the quality assurance of the period of use of the device and also the quality of the examination results using the device. As a suggestion for implementing tool maintenance, testing and calibration of health devices should not only be to fulfill existing regulations or regulations. However, the most important thing is how to guarantee the quality of medical services and patient safety.